Feasibility of establishing a core set of sexual, reproductive, maternal, newborn, child, and adolescent health indicators in humanitarian settings: results from a multi-methods assessment in Bangladesh - Bachera Aktar; Kanya Lakshmi Rajendra; Emily Clark; Kassandre Messier; Anya Aissaoui; Kaeshan Elamurugan; Md. Tanvir Hasan; Nadia Farnaz; Adrita Kaiser; Abdul Awal; Ieman Mona El Mowafi; Loulou Kobeissi (BMC, 2022)
Plain English Summary Reliable data on sexual, reproductive, maternal, newborn, child and adolescent health (SRMNCAH) in humanitarian settings is very important for addressing the needs of the refugee population. However, the quality of data collected often varies across different humanitarian settings and organizations. To address this gap, WHO developed a core set of indicators, through global consultations and field-level assessments, for monitoring and evaluating SRMNCAH services and outcomes in humanitarian settings. In Bangladesh, the feasibility assessment was conducted in Rohingya camps in Cox's Bazar and assessed the feasibility in terms of relevance/usefulness of the indicators, feasibility of measurement, availability of systems and resources for data collection, and data collection and management related ethical issues in the Rohingya context in Bangladesh. The field-level assessment applied a multi-method approach including a desk review, key informant interviews, focus group discussions, and facility assessments. The findings revealed existing multiple sources and vertical systems of data collection by different organizations and the indicators also varied depending on the requirements of the Bangladesh government, donor agencies, UN agencies leading different sector/sub-sectors/clusters, and organizations' own priorities and mandates. All the stakeholders who participated in this study agreed on developing a harmonized and standardized core set of SRMNCAH indicators. However, they raised concerns regarding the adaptation of the core set of indications to the local context. They also emphasized on the importance of adequate resources for establishing strong reporting and data management systems, capacity development of human resources and the buy-in from the international community for effective implementation.